Analysis of facial bone fractures: An 11-year study of 2,094 patients - Hwang Kun; You Sun (Indian Journal of Plastic Surgery)
Purpose: The medical records of these patients were reviewed and analysed to determine the clinical characteristics and treatment of facial bone fractures. Patients and Methods: This is a retrospective study of 2,094 patients with facial bone fractures from various accidents that were treated at the Inha University Hospital from 1996 to 2007. Results: The most common age group was the third decade of life (29%). Males were more common than females (3.98:1). The most common aetiology was violent assault or nonviolent traumatic injury (49.4%). The most common isolated fracture site was the nasal bone (37.7%), followed by the mandible (30%), orbital bones (7.6%), zygoma (5.7%), maxilla (1.3%) and the frontal bone (0.3%). The largest group with complex fractures included the inferior region of the orbital floor and zygomaticomaxilla (14%). Closed reduction was performed in 46.3% of the cases while 39.7% of the cases required open reduction. For open reductions, the most commonly used soft-tissue approach was the intraoral approach (32.3%). The complication rate was 6.4% and the most common complication was hypoesthesia (68.4%) followed by diplopia (25.6%). Conclusion: Long-term collection of epidemiological data regarding facial fractures and concomitant injuries is important for the evaluation of existing preventive measures and useful in the development of new methods of injury prevention and treatment.